2016
DOI: 10.1371/journal.pone.0167247
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema Distribution and Diffusion Capacity Predict Emphysema Progression in Human Immunodeficiency Virus Infection

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) and emphysema are common amongst patients with human immunodeficiency virus (HIV). We sought to determine the clinical factors that are associated with emphysema progression in HIV.Methods345 HIV-infected patients enrolled in an outpatient HIV metabolic clinic with ≥2 chest computed tomography scans made up the study cohort. Images were qualitatively scored for emphysema based on percentage involvement of the lung. Emphysema progression was defined as any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Certain clinical risk factors beyond HIV-specific variables have been associated with worse trajectory. One study assessing the qualitative assessment of radiographic emphysema over several years of follow-up found that 17% of participants progressed, with risk factors for progression including baseline presence of combined centrilobular and paraseptal emphysema (present in 23% of the cohort), worse DLco, high pack-years smoked, male sex, and lower BMI [99] . While single-center cross-sectional studies found associations between ART use and COPD, a large prospective study evaluating pulmonary function decline in association with initiation of ART found no difference in rate of lung function decline between people randomized to initiate ART at CD4 cell counts > 500 cells/uL versus at CD4 cell counts < 350 cells/uL [69] .…”
Section: Non-infectious Pulmonary Complications Of Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain clinical risk factors beyond HIV-specific variables have been associated with worse trajectory. One study assessing the qualitative assessment of radiographic emphysema over several years of follow-up found that 17% of participants progressed, with risk factors for progression including baseline presence of combined centrilobular and paraseptal emphysema (present in 23% of the cohort), worse DLco, high pack-years smoked, male sex, and lower BMI [99] . While single-center cross-sectional studies found associations between ART use and COPD, a large prospective study evaluating pulmonary function decline in association with initiation of ART found no difference in rate of lung function decline between people randomized to initiate ART at CD4 cell counts > 500 cells/uL versus at CD4 cell counts < 350 cells/uL [69] .…”
Section: Non-infectious Pulmonary Complications Of Hivmentioning
confidence: 99%
“…HIV has been shown to be an independent risk factor for DL CO impairment in cohorts including HIV-infected and uninfected participants in both the pre- and post-ART eras [30, 66] . Interestingly, while in many cases DL CO impairment is seen in association with abnormal spirometry or radiographic emphysema [30, 66, 99, 100] (and therefore likely to represent lung disease), significant DL CO impairment is also found with normal spirometry, suggesting another pathophysiology driving gas exchange impairment in these participants [30, 48, 66, 97] (Figure 2). Certain cohorts have found diffusing impairment to correlate with abnormal echocardiogram findings, with increased tricuspid regurgitant velocity (TRV) suggesting elevated pulmonary artery pressures or cardiopulmonary dysfunction as a contributor [36, 100] , but a significant portion of HIV-infected individuals have neither COPD nor cardiac dysfunction to explain their DLco impairment.…”
Section: Non-infectious Pulmonary Complications Of Hivmentioning
confidence: 99%
“…The rationale of screening also depends on the possible interventions that could be envisaged for high‐risk individuals. In a previous study in both smokers and never‐smokers attending the MHMC, we were able to demonstrate a progression of CT findings potentially associated with adverse health outcomes . Closer disease monitoring could be applied in high‐risk patients to identify lung disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that, of 1,446 HIV-infected patients on ART in their cohort, nearly 50% had evidence for emphysema and/or bronchiolitis based on thoracic computed tomography (CT) scans, with 13% showing signs of bronchiolitis, 19% showing emphysema, and 16% having both ( 161 ). Furthermore, among ART-treated HIV-infected participants recruited by Leung et al., emphysema progression was not associated with peripheral CD4 cell counts or CD4:CD8 ratio, HIV viral load, ART classes or duration of ART exposure ( 162 ). As proposed by others, the increase in incidence rate of chronic inflammatory conditions in the ART era, of not just emphysema and COPD but also diabetes and cardiovascular disease, can largely be explained by improved life expectancies in treated PLWH, giving them more time to develop these co-morbidities ( 163 , 164 ).…”
Section: Accelerated Pulmonary Co-morbidities During Hiv Infectionmentioning
confidence: 99%